Fixed-bed drying of rice with airflow reversal for product quality and drying performance - Rashti, Kobra Tajaddodi Talab (2012)
In Malaysia, paddy is typically harvested at moisture contents (MC) of around 21% to more than 30% (w.b.) and is dried to 13 – 14 % by using the fixed bed dryer (one direction airflow) at drying air temperature of 42 - 45 °C and grain bed depth of around 100 cm. As drying progresses in this type of dryer, grains near the air inlet are equilibrated with heated air and become over-dried before the grains in top layers reach the target final moisture content (FMC). This leads to non uniformity of grain MC within the entire bed at the end of drying operation. The main objective of this study is to improve drying process of rough rice using fixed bed drying method by reversing the airflow direction. In order to evaluate the effect of airflow reversal drying method on rice quality and drying performance, a laboratory experimental dryer was designed and fabricated. The approach was initiated by modifying an existing computer simulation procedure for fixed bed drying to meet the purpose of this study. Matlab software was applied to write the computer simulation program. Graphic User Interface (GUI) was created to show the simulation results graphically and numerically. The maximum bending strength was close to 35.69 MPa and 33.64 MPa for 55 °C and 60 °C, respectively. The results also revealed that drying air temperature of 40 °C and FMC range of 12 – 13.5% could be appropriate selections to achieve high whole kernel percentage (WKP) for a Malaysian paddy variety (MR219). Glass transition temperature (Tg) for MR219 was observed to be in the range of 9.65 - 61.79 °C, with MC in the range of 26.8 – 7.4% (w.b.). Results fit ability of Zuritz equation showed that it would be suitable to represent equilibrium moisture content (EMC) for computer drying simulation and its parameters were modified based on MR219. Results of the computer drying simulation that were depicted on glass transition diagram revealed that drying air temperature of 50°C can be recommended as the first temperature to dry paddy with high initial moisture content (above 30%) for 2.20 h in two-stage drying of MR219. Reversing the direction of airflow every 2 or 3 h cannot be recommended especially for high moisture grain due to occurrences of several transitions from rubbery to glassy state and vice versa, as well as several moisture readsorption and re-desorption for grains in the top and bottom layers of the dryer during the entire drying process. The results illustrated that HRY could be improved by changing the airflow direction when MC of grains at bottom layers were above 12%, and at top layers were about 17 – 18% with grain bed depth of 50 cm. In this drying scenario, applying the downward drying air temperature of 36 °C – 36.5 °C may not cause significant HRY reduction after changing the direction of airflow. Generally, the results showed that drying capacity by airflow reversal drying increased above 20%. Electricity costs decreased 20.44%, 11.99%, 32.33%, 25.17%, and 18.26% for airflow reversal drying with grain depth of 100 cm, 75 cm (G= 59 m³/min. t), 75 cm (G= 28 m³/min. t), 50 cm (G= 59 m³/min. t), 50 cm (G= 35 m³/min. t), respectively compared to conventional drying. In order to minimize undesirable effects of high drying rate, recommended superficial velocity and airflow rate ranges could be 0.18 – 0.22 m/s and 43 – 52 m³/min .t, respectively, for airflow reversal drying with grain bed depth of 50 cm. Although airflow reversal drying with grain depth of 75 cm and airflow rate of 28 m³/min. t showed more HRY reduction than that of 50 cm drying treatments, but good results of that treatment compared to the other drying treatments (grain bed depth of 75 and 100 cm) indicated HRY could be improved by adjusting the grain bed depth, superficial air velocity (maximum 0.2 m/s) and related airflow rate.